Assessment of Efficiency of Mutual Funds - Dr. S. Neelima, Dr. P. Lakshmi Narayanamma (International Journal of Advanced Science and Technology, 2020)
The present study employs Data Envelopment Analysis (DEA) to benchmark selected 32 top mutual fund schemes on their efficiency. DEA is a nonparametric method which measures the relationship of inputs utilized and output produced with an efficiency score. The study has been conducted by employing six inputs and two outputs. Inputs include minimum investment, expense ratio, exit-load, age of the mutual fund, asset size and beta. Outputs include Sharpe’s value and Treynor’s index value. The efficiencies with respect to Variable Returns to Scale, Constant Returns to Scale, and Scale Efficiency were calculated. The efficiency score from DEA analysis compares mutual fund schemes to the schemes which are performing best. The study helps to identify efficient schemes so that investor can choose efficient fund to get good returns. Further, this paper generates efficient peers with corresponding weights and target values for all the selected mutual funds for their improvement.